Edukasi Pemanfaatan Buah Naga Merah sebagai Upaya Pencegahan Anemia pada Ibu Hamil - Andriani, Rezah (IKesT Muhammadiyah Palembang, 2024)
Iron requirements increase during pregnancy due to fetal and placental requirements and physiological changes such as increased blood volume and red blood cell count. An increase in these levels can also lead to a decrease in hemoglobin and hematocrit levels, resulting in increased prevalence of anaemia and iron deficiency in pregnancy. Dragon fruit is a fruit that is rich in antioxidants and calcium and is relatively high in iron. The purpose of the community service activities that will be carried out is to provide education about the use of red dragon fruit as an attempt to prevent anemia in pregnant mothers and is planned to be implemented on Monday, January 29th, 2024 in Bidan Nurachmi Palembang Independent Practice. The method of community dedication is by giving the approval, the participants of this community service activities are pregnant mothers of Trimester I to III of 10 people. All participants followed the activity from start to finish, were active in the discussion, and were well evaluated. Evaluation is done with pre and post test assessments by filling in the questionnaire that has been provided. The pre-test assessment results obtained an average score of 51 and an average post-test score of 86, from the evaluation results can be concluded there was an increase in the average score participants so there is an improvement in knowledge and understanding about the use of red dragon fruit as an attempt to prevent anemia in pregnant mothers.